Court protection of workplace accidents regarding the prevention of occupational hazards - López Ahumada, José Eduardo (2022)
This research analyzes the possibilities of workplace accidents protection from the perspective of the occupational risk prevention, as well as its main points of connection. Indeed, there is a relationship of communicating vessels between this prevention and the regulatory response to occupational contingencies. Likewise, the link between labor-related damages and occupational contingencies is evident by virtue of the regulatory treatment provided by the occupational risk prevention legislation. For these purposes, we must take into account the following labor-related damages: diseases, pathologies, as well as injuries sustained as a result of or in connection with work. In this sense, labor-related damages are an outcome that is constantly tried to avoid, and, to this end, its prevention is encouraged from a regulatory point of view.